(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
In order to ensure the financial sustainability of companies under current economic conditions successful management of current assets is crucial. In practice it is quite often observed that the decisions related to current assets management in Latvian companies are made in the short-term aspects without making analysis. Efficient management of working capital is an essential condition of rise in profitability of a company. Potentialities of working capital management in the context of efficient running of business have not been studied in Latvia up until now. The main aim of this article is to examine the effect of working capital on profitability of Latvian companies. The results of the research that has been performed in relation to Latvian enterprises confirm the existence of a correlation between components of working capital and profitability. The developed regression equations meant for forecasting profitability of a company applying working capital management methods can be used by Latvian enterprises. It follows that managers of an enterprise can forecast indexes characterizing profit, managing components of working capital and maintaining it on the optimum level